Blended Learning with Jigsaw in Increasing Interest, Motivation, and Learning Outcomes in Sports Sociology Learning - Yahya Eko Nopiyanto; Ari Sutisyana; Septian Raibowo; Yarmani Yarmani (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
The purpose of this study was to increase the interest, motivation, and learning outcomes of students in learning  sports sociology by applying blended learning with  the jigsaw method. The research method used was an action  classroom with two cycles. The research subjects were students of  the fifth semester with a total of 39 students. The results showed that in the pre-cycle students' interest in learning was in the low category, learning motivation was  in the sufficient category. The results of cycle 1 showed that interest in learning  student increases in the high category with a percentage of  70%, learning motivation was in the high category with a percentage of  75%, learning outcomes were in the high category with a percentage of 70%.  The results of cycle 2 showed that student interest in learning increases in  the high category with a percentage of 80%, learning motivation was in  the high category with a percentage of 85%, learning outcomes were in the category  high with a percentage of 85%. So it can be concluded that the  application of blended learning with the jigsaw method can  increase the interest, motivation, and learning outcomes in learning sports sociology.